Kompensasi dan Imbalan Digital: Membangun Sistem Kinerja, Bonus, dan Pendekatan Fleksibel untuk Penghargaan Karyawan di Era Digital - Iwanussoleh Iwanussoleh; Ristin Dea Ananda Gesta; Rina Marliana; Bilqis Maharani Qodri; Mochammad Isa Anshori (Jurnal Manajemen dan Ekonomi Kreatif, 2023)
Purpose − In the ever-evolving digital era, the paradigm of employee compensation and rewards is also undergoing a fundamental transformation. Digital Compensation and Rewards concepts have emerged as a response to these changes, with a focus on building adaptive performance systems, innovative bonus approaches, and flexibility in employee rewards. Overall, the Digital Compensation and Rewards paradigm brings modern concepts to human resource management. In the digital era, employee compensation and reward systems are experiencing fundamental changes. The use of technology allows for more efficient implementation of performance-based systems. Findings- The results of the literature review show that technology has a significant positive impact on the employee recruitment stage. Apart from that, the implementation of digital compensation and rewards is also an integral part of employee performance. Design/methodology/approach- By using data-based performance assessments with digital platforms, companies can collect and analyze employee performance data in more detail. This allows for more objective and accurate assessments, as well as providing opportunities for appropriate recognition of individual contributions. Practical implications- Involves improving the recruitment process through the use of digital technology and social media, adjusting the compensation system to include digital performance bonuses and application-based incentives, flexibility in providing rewards tailored to individual preferences, the use of data and analysis to measure employee performance accurately, as well as development of HR skills in integrating digital technology in human resource management. By paying attention to these practical implications, companies can improve their human resource management strategies to face the challenges and opportunities in the digital era, which can support organizational growth and success. Originality/value- This research presents an innovative view of how organizations can use digital technology and more flexible bonus systems to increase employee motivation and productivity. With a focus on the digital era, this paper provides insight into the importance of adapting to technological changes in human resource management. The value of this paper is that it provides practical guidance for companies seeking to improve their human resource management strategies to optimize employee performance and rewards in the ever-changing digital era.